Solo leveling. 6 - Chugong; Torres, J., 1969- (Ize Press, 2023)
With Esil the demon noble's guidance and his shadow army by his side, Jinwoo's making his way up the floors of the Demon Castle at a breakneck pace. At this rate, it won't be long before he reaches the top floor to face Balan the Demon Monarch. Meanwhile, on the other side of the gate, an unexpected and most unwelcome magic beast is spotted on the shores of Japan...